2021
DOI: 10.1364/oe.423870
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the effect of atmospheric turbulence on orbital angular momentum-based quantum key distribution using real-time adaptive optics with phase unwrapping

Abstract: Quantum key distribution (QKD) employed orbital angular momentum (OAM) for high-dimensional encoding enhances the system security and information capacity between two communication parties. However, such advantages are significantly degraded because of the fragility of OAM states in atmospheric turbulence. Unlike previous researches, we first investigate the performance degradation of OAM-based QKD by infinitely long phase screen (ILPS), which offers a feasible way to study how adaptive optics (AO) dynamically… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Based on the infinitely long phase screen [42,43], we design a computer code of CGI through atmospheric turbulence to investigate the scintillation effect, the aperture averaging effect, and the imaging quality. In this model, the light source (wavelength λ = 632 nm and size ρ s = 0.01 m) generated by a CW laser propagates through paths that are all horizontal links with the distance z 0 = z 1 = z 2 = 2000 m. The atmospheric coherence length r 0 is known as an ensemble quantity that describes the average strength of the atmospheric turbulence over the propagation path z i and can be written as:…”
Section: Influence Of the Atmospheric Coherence Length Rmentioning
confidence: 99%
“…Based on the infinitely long phase screen [42,43], we design a computer code of CGI through atmospheric turbulence to investigate the scintillation effect, the aperture averaging effect, and the imaging quality. In this model, the light source (wavelength λ = 632 nm and size ρ s = 0.01 m) generated by a CW laser propagates through paths that are all horizontal links with the distance z 0 = z 1 = z 2 = 2000 m. The atmospheric coherence length r 0 is known as an ensemble quantity that describes the average strength of the atmospheric turbulence over the propagation path z i and can be written as:…”
Section: Influence Of the Atmospheric Coherence Length Rmentioning
confidence: 99%
“…The proposed protocol utilizes adaptive optics and a phase-randomized reference beam to mitigate the effect of turbulence on the key generation rate. In a study by Vishal Sharma, [33], the authors investigated the effect of channel noise on QKD in UWOC. The study showed that QKD is robust to channel noise in UWOC, but the key generation rate decreases as the noise level increases.…”
Section: Focused Study On Qkd Key Generation Ratementioning
confidence: 99%